2015
DOI: 10.1002/app5.97
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the Role of Parental Education in the Regional Variations in Infant Mortality in India

Abstract: Using data from the National Family Health Survey (2005-06)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 41 publications
(48 reference statements)
3
13
0
Order By: Relevance
“…However, our study found that parental education has protective effects on childhood mortality suggesting the parental education remains important in relation to childhood mortality in Myanmar. The findings also reinforce other evidence of protective effects of parental education on childhood mortality in Tanzania [30], India [33] and Palestine [44].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, our study found that parental education has protective effects on childhood mortality suggesting the parental education remains important in relation to childhood mortality in Myanmar. The findings also reinforce other evidence of protective effects of parental education on childhood mortality in Tanzania [30], India [33] and Palestine [44].…”
Section: Discussionsupporting
confidence: 86%
“…With respect to parental education, many studies report that parental education is associated with the families' socioeconomic circumstances and that parents' health knowledge and behaviours can impact on child health and survival [15,[32][33][34][35][36][37][38][39][40][41][42][43]. A recent study that used DHS data from 43 LMICs, reported that the role of parental education in child health has attenuated considerably over time (1991 to 2016) in low resource settings and that the association between mother's education and child health is weakening in line with societal changes [17].…”
Section: Discussionmentioning
confidence: 99%
“…Education is considered as an important social determinant of health and there is abundant evidence of the positive relationship between education and health status of the people. 13 Kerala's literacy rate is 93.91% and its IMR is only 10 per 1000 live births. Providing education to the parents, particularly to mothers is critical to reduce infant mortality rates and its regional variations in India.…”
Section: Discussionmentioning
confidence: 99%
“…Providing education to the parents, particularly to mothers is critical to reduce infant mortality rates and its regional variations in India. 13 The interviewees believed that the awareness among the parents in Manipur is also a contributing factor in the low IMR in the state. According to them, the parents are acquainted with the benefits of regular ante natal checkups, timely immunisation, institutional deliveries, etc.…”
Section: Discussionmentioning
confidence: 99%
“…This association has been attributed, in part to increased awareness, adoption of safe behavioral practices and prompt access to preventive and curative health services by the more educated individuals [13]. Several existing evidence in support of the positive impact of education on better health outcomes are available [11, 14, 16, 26, 27], most of them suggest that education attainment imparts similar influences on HIV burden, reduced child mortality and increased survival.…”
Section: Introductionmentioning
confidence: 99%